Modulation of ovarian response in anoestrus cattle treated with insulin alone and in combination with gonadotropin releasing hormone - SHUKLA, S N; AGARWAL, S K; SHANKER, U; VARSHNEY, V P; MAJUMDAR, A C (The Indian Journal of Animal Reproduction, 2023)
The influence of insulin alone and in combination with gonadotropin releasing hormone (GnRH) on ovarian response as well as glucose and progesterone-profile was studied on 28 anoestrus cows divided randomly into 4 groups i.e. insulin treatment (G-1), GnRH treatment (G-11), insulin plus GnRH (G-111) and control (G-IV);- each comprising 7 aeim.alli lu insu..li.n treatment group cows were injected subcutaneously long acting purified bovine insulin at 0.25 JU/leg body weight/day for 5 consecutive days. In GnRH treatment group cows were injected intramuscularly single IO μg dose of busereline acetate. In insulin + GnRH treatment group cows were injected insulin for 5 days similar lo G-1 and a single injection of GnRH 48 hrs after the last insulin injection. In control group cows were not administered any drug. The induction of estrus was higher in insulin treated cows (85.7%) (P<0.05) as compared lo GnRH (57.14%), insulin + GnRH (42.85%) and control (14.3%). A remarkable degree of conception was recorded using insulin in anoestrus cows. Overall conception rate was 40, 100 and 33.3% in G-1, -II and -III, respectively, none got conceived in control group. The plasma glucose concentration was at the normal level before start of treatment (43,500:tl.552 to 51.243±2.932 mg/di) and did not significantly differ among the groups during different days of treatment. Serum progesterone concentration was al the basal level (<I ng/ml) before start of treatment; day S, 10 and 15 after treatment in all the groups, progesterone concentration was lowest al estrus and thereafter, ii increased at higher level in insulin treatment group (7.11 S:tO. 723 ng/ml) as compared to GnRH (5.660:t0.315 ng/ml), insulin + GnRH (4.160:t0.834 ng/ml) and control (3.59±0.00 ng/ml) (P>0.01). These results indicated beneficial effects of insulin on ovarian response and restoration of fertility in anoestrus cattle.